Strategi Digital Marketing pada Lembaga Kursus dan Pelatihan Vision College - Yunita Sinta Amanda; Bagus Kisworo (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The existence of internet technology and social media makes digital marketing strategies very important for institutions, especially courses and training institutions that have very fierce competition because of the many competitors that appear every year. This study aims to describe: 1) The implementation of digital marketing strategies at LKP Vision College, and 2) Describe the supporting factors and inhibiting factors for the success of digital marketing strategies at LKP Vision College. This research uses qualitative research methods that refer to Sugiyono's research model. In collecting data using interview techniques, observation, and documentation. then data processing using data triangulation and source triangulation. From this research, the results were obtained: 1) The Marketing model used is the Segmenting, Targeting, and Positioning (STP) model, the Search Engine Optimation (SEO) model, and the Social Media Marketing (SMM) model. 2) Then the digital marketing strategy used is the Strenght, Weakness, Opportunity, and Threats (SWOT) strategy, and the 7p Marketing mix strategy. 3) There are several factors that support the implementation of LKP Vision College's digital marketing strategy, including human resources and infrastructure. While inhibiting factors include funding and interpersonal communication